Art rock concert practice and its projection into the XXIst century - Romanko, Volodymyr (Scientific herald of Tchaikovsky National Music Academy of Ukraine, 2019)
Relevance of the study. In the space of modern music, a special cluster is formed by the classics of art rock – musical works that were created during the end of the 1960s – the first half of the 1970s and haven’t yet lost their artistic value, force of conviction and power of influence over their audience. Though mostly reproduced as records nowadays, they are still often used at concerts forming a special stream of modern music life. A come-back of the highest achievements of art rock being at the interface between the entertaining and the academic music and bearing the high artistic and intellectual value into the concert practice requires careful attention from researchers. The main objective of the study is to describe the specifics of concert practice of art rock at runtime, from the classic period till the last twenty years’ period. Methodology. The main in the study is the comparative method that allows us to clarify the similarities and the differences in presentation of art rock musical works at the different stages of the musical cultural process. Results and conclusions. The study allowed us to describe some parameters of the process of change of art rock concert practice. The classic period of art rock that is from the second half of the 1960s till the mid-1970s was marked by substantial difficulties in an arrangement of shows including those related to incompleteness of instruments. As a result, the depth and scale of the author's intention contradicted the real possibilities of its implementation, which stimulated the search for successful problem solving. Closer to the 1980s, art rock divides into layers: some bands go out of existence or make a long break in their activities, the others slightly change their style focus. Not all but just a few art rock representatives have stayed true to themselves. At the beginning of the XXIst century, with a rising tide of interest towards the classics of art rock on a concert stage, for a number of reasons it leaks away its authenticity as an artistic phenomenon in which the composer and the singer are impersonated all in one.